2021
DOI: 10.1021/acs.molpharmaceut.1c00224
|View full text |Cite
|
Sign up to set email alerts
|

Prodrug Delivery Using Dual-Targeting Nanoparticles To Treat Breast Cancer Brain Metastases

Abstract: Brain metastases from breast cancer are the most frequent brain metastasis in women, which are often difficult to be surgically removed due to the multifocal and infiltrative intracranial growth patterns. Cytotoxic drugs have potent anti-breast cancer properties. However, owing to the toxic side effects and the blood−brain barrier (BBB), these drugs cannot be fully and aggressively exploited with systemic administration and hence have very limited application for brain metastases. In this study, hyaluronidase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…45 To be effective at both tumor extravasation and cancer cell uptake, some nanoparticles are equipped with transcytosistargeting peptides and cancer cell-targeting ligands to target both vasculature and cancer cells simultaneously. 46 Alternatively, there are also receptors overexpressed by both cancer cells and vasculature cells such as the glucose transporter (GLUT) receptor. Nanoparticles equipped with glucose as a targeting ligand exhibited improved performance in both vascular translocation and cancer cell uptake.…”
Section: Popular Tumor-targeting Strategiesmentioning
confidence: 99%
“…45 To be effective at both tumor extravasation and cancer cell uptake, some nanoparticles are equipped with transcytosistargeting peptides and cancer cell-targeting ligands to target both vasculature and cancer cells simultaneously. 46 Alternatively, there are also receptors overexpressed by both cancer cells and vasculature cells such as the glucose transporter (GLUT) receptor. Nanoparticles equipped with glucose as a targeting ligand exhibited improved performance in both vascular translocation and cancer cell uptake.…”
Section: Popular Tumor-targeting Strategiesmentioning
confidence: 99%
“…To enhance the specificity of NPs to the BCBM tumor microenvironment (TME), Ju et al manufactured PLGA‐PLL‐based NP shells that were co‐functionalized with HA and transcytosis‐targeting peptide (TTP) 46 . These dual‐targeting NPs were proposed to efficiently cross the BBB via TTP‐mediated binding to heparin sulfate proteoglycans, followed by BCBM uptake through HA binding to CD44 expressed on BCBM cells.…”
Section: Functionalized Nanoparticles To Enhance Drug Delivery To Bcbmmentioning
confidence: 99%
“…Using nanoparticles modified to target PSMA and loaded with doxorubicin and lapatinib, the authors showed that the PSMA-targeted NPs had a 4.57-fold increase in tumor penetration compared to the unmodified NPs. Moreover, the median overall survival of mice treated with the PSMA-targeted NPs increased to 44 days vs 29 days for nontargeting NPs.To enhance the specificity of NPs to the BCBM tumor microenvironment (TME), Ju et al manufactured PLGA-PLL-based NP shells that were co-functionalized with HA and transcytosis-targeting peptide (TTP) 46. These dual-targeting NPs were proposed to efficiently cross the BBB via TTP-mediated binding to heparin sulfate proteoglycans, followed by BCBM uptake through HA binding to CD44 expressed on BCBM cells.…”
mentioning
confidence: 99%
“…The BBB strictly controls the material exchange between blood and brain, and hinders the delivery and accumulation of therapeutic drugs for intracranial diseases, making it difficult for brain-targeted drug therapies to achieve the expected effect. 120,121 In recent years, many nanotechnology-related studies have been devoted to the effective intracerebral delivery of therapeutic drugs for brain diseases, 122 such as the DDS based on low density lipoprotein receptor associated protein (LRP1) 123 and prostatespecific membrane antigen (PSMA) that can mediate endocytosis, 124 the DDS based on activating endothelial cell K ATP to promote BBB permeability, 125 the DDS that regulates endothelial Mfsd2a to antagonize its inhibition of transcytosis, 126,127 and the DDS that avoids basal LRP1 mediated brain clearance, etc. 128 However, the brain targeting efficiency is still not enough to achieve efficient treatment.…”
Section: Drug Deliverymentioning
confidence: 99%